Investigation of ductile iron in mold treatment process parameter - Yap, Min Choo (2009)
Ductile iron was first developed in 1943 and it is widely used in automotive industry.The difference between cast iron and ductile iron is due to the presence of spheroid graphite in the matrix of ductile iron which is not found in brittle cast iron. Ductile iron possesses higher ductility and tensile strength than in cast iron. It is inexpensive and castability compared to steel. Magnesium is an effective nodularization agent and it is added into the molten iron to produce nodular shape of cast iron. This is happened through a mechanism called heterogeneous nucleation.In this project, it is divided into two stages, foundry laboratory and parameters investigation. Magnesium ferrosilicon is used as the nodularization agent for the nodularization process. “In mould” treatment is a method of late inoculation. A special reaction chamber is built and placed in the gating system. This is an effective technique to obtain highest magnesium recovery and eliminate fading problem. The production of ductile iron is obtained through sand casting process. It is controlled by using different amount of magnesium ferrosilicon and casting size. Then, the ductile iron casting is investigated to observe corresponding material behaviour and mechanical properties through hardness test and metal analysis. As a result, these parameters are significantly influence on the nodularization of ductile iron casting.